Expert Oracle Exadata - Osborne, Kerry; Johnson, Randy; Poder, Tanel (Apress : Imprint: Apress, 2011)
Throughout history, advances in technology have come in spurts. A single great idea can often spur rapid change as the idea takes hold and is propagated, often in totally unexpected directions. Exadata embodies such a change in how we think about and manage relational databases. The key change lies in the concept of offloading SQL processing to the storage layer. That concept is a huge win, and its implementation in the form of Exadata is truly a game changer. Expert Oracle Exadata will give you a look under the covers at how the combination of hardware and software that comprise Exadata actually work. Authors Kerry Osborne, Randy Johnson, and Tanel Põder share their real-world experience, gained through multiple Exadata implementations with the goal of opening up the internals of the Exadata platform. This book is intended for readers who want to understand what makes the platform tick and for whom-"how" it does what it is does is as important as what it does. By being exposed to the features that are unique to Exadata, you will gain an understanding of the mechanics that will allow you to fully benefit from the advantages that the platform provides. Changes the way you think about managing SQL performance and processing Provides a roadmap to laying out the Exadata platform to best support your existing systems Dives deeply into the internals, removing the "black box" mystique and showing how Exadata actually works.